Why Do Women Pretend to Be Men? Female Gender Swapping in Online Games - Zhou, Liling; Han, Ning; Xu, Zeran; Brian, Corlyn; Hussain, Siraj (Frontiers in Psychology, 2022)
This research explored the influencing factors of gender swapping among female players in online games and their impact on online gaming behavior. Based on an online survey of 3,658 female players in China, we found that perceived benefits and the Tanbi tendency, a psychological indulgence in enjoying novels, comics, or series on love and sex between attractive males, were the most important factors for female players to employ male avatars. Sexual orientation, perceived anonymity, and perceived tolerance also had a significant influence on gender swapping. Different from the practical benefits perceived by men who use female avatars in online games, the perceived benefit for female players who use male avatars was to avoid gender discrimination. In order to obtain more freedom and fairer treatment, they chose male avatars for a better experience. Female players with a higher degree of gender swapping showed a stronger aggressiveness and dominant “hyper-masculinity” behavior tendency in the game. Though online virtual worlds may be a convenient place for females to experience gender equality through gender swapping, the findings of this study suggest that gender swapping in games may, to some extent, perpetuate or even reinforce gender stereotypes in the real world.